Construction of a highly flexible head and neck phantom (Transactions on Additive Manufacturing Meets Medicine, 2019)
Commercially available phantoms for radiotherapy have the disadvantage to be not adaptable to various specific issues. Additive manufacturing has evolved rapidly in the last few years. Nowadays it is accessible and cost-effective. The head and neck phantom presented here contains a dentition for the study of metal artifacts in both, computed tomography and radio therapeutic dose distribution. The phantom is designed in layers for being quickly adaptable to other issues. Bone and soft-tissue boundaries were three dimensional printed and replenished with tissue equivalent materials.